2017
DOI: 10.1038/s41598-017-16348-8
|View full text |Cite
|
Sign up to set email alerts
|

Creation and Annihilation of Skyrmions in the Frustrated Magnets with Competing Exchange Interactions

Abstract: In triangular-lattice magnets, the coexistence of third-neighbor antiferromagnetic and nearest-neighbor ferromagnetic exchange interactions can induce rich magnetic phases including noncoplanar skyrmion crystals. Based on Monte Carlo simulation, we studied the dependence of magnetic phase transition on exchange interaction strength. Under the consideration of uniaxial anisotropy and magnetic field both perpendicular to the film plane, a large antiferromagnetic exchange interaction induces a high frustration. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…For the frustrated triangular model with J 1 -J 2 or J 1 -J 3 , rich phase diagrams have been reported [53,54,61,66]. Fig.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…For the frustrated triangular model with J 1 -J 2 or J 1 -J 3 , rich phase diagrams have been reported [53,54,61,66]. Fig.…”
Section: Resultsmentioning
confidence: 93%
“…For the frustrated triangular model with J 1 -J 2 or J 1 -J 3 , rich phase diagrams have been reported [53,54,61,66]. Under the consideration of uniaxial anisotropy and magnetic field both perpendicular to the lattice plane (e k and e h along +z direction), the perpendicularly magnetized (PM) skyrmion crystal emerges at intermediate h and above a small k, and remains down to zero-temperature.…”
Section: Resultsmentioning
confidence: 99%
“…SKs form double-twist solitonic structures, offering many perspectives in spintronics and data storage [27,28]. As predicted by theory [29][30][31][32][33], some anisotropic ordered magnets with competing nearest neighbor (NN) and next nearest neighbor (NNN) exchange interactions may host localized SKs with versatile internal structure and smooth rotation of the magnetization. Different types of modulated phases such as hexagonal or square SK lattices have been predicted, yielding a very rich phase diagram [30].…”
Section: Reentrant Spin Glasses and "Frustrated" Skyrmionsmentioning
confidence: 97%
“…This allows individual skyrmions to exist as metastable states, which has been brought to light in recent experiments [26]. Moreover, it has been shown that a variety of antiskyrmion states (q = −1, −2) are also metastable when frustrated exchange interactions are taken into account in such ultrathin films [27][28][29][30] and more generally in bulk chiral magnets [31,32], which lead to an attractive interaction between skyrmions [33]. We employed density-functional theory calculations to obtain estimates of the exchange, anisotropy, and DMI energies for PdFe/Ir(111), which were then used to parametrise an atomistic spin model for studying the dynamics (see Methods).…”
mentioning
confidence: 99%